Effects of Gamma Radiation on Mature Larvae of Pectinophora gossypiella (Saunders) and their F1 Progeny - S. Shahzad Ali,; Huma Rizwana,; S. Sohail Ahmad,; Imran Hassan,; S. Shahbaz Ali, (Journal of Basic & Applied Sciences, 2014)
The mature larvae of Pectonophora gossypiella (Saunders) obtained from the laboratory culture maintained on casein wheat germ diet were irradiated at 35, 45, 55 and 65 Gy doses at a dose rate of 30.8 Gy/min. in a Cs-137 gamma irradiator. The pupation was delayed as the radiation dose increased. Furthermore, larval survival to pupal and adult stages were also susceptible to gamma radiation doses were increased. Females were more susceptible to gamma radiation than males. The effect of gamma radiation on reproduction in P1 moths following irridation of mature larvae was dose dependent. As the dose of mature larvae increased, average egg production, hatch percentage and adult longevity reduced. Egg production, was reduced more drastically in the crosses Untreated Male x Treated Female (UTM x TF) and Treated male x Treated Female (TM X TF) than the crosses Treated Male x Untreated Female (TM x UTF). Complete sterility was recorded when treated males were paired with treated females at 45 Gy and higher doses of gamma radiation. The results on the egg production, hatch percentage and adult longevity of F1progeny of male parents following irridation of mature larvae showed that egg production was reduced significantly in crosses UTM x F1 Female at 35 Gy and complete sterility was recorded at higher doses. In crosses F1 Male x F1Female, complete sterility was recorded at all the test doses of gamma radiation. The radiation doses higher than 35 Gy were more lethal either in F1 Male x F1 Female. The adult longevity was unreliable in all the crosses. However, moths were short-lived in both F1 Male x F1 Female and UTM x F1 Female progeny of treated pink bollworm females crossed with untreated males following irradiation of mature larvae indicated similar results as recorded in the case of male treated parents. However, complete sterility was recorded in F1 Male x F1 Female and UTM x F1 Female crosses and a few eggs were laid in F1 Male x F1 Female crosses at 35 Gy dose with 14.76 percent egg hatch.